2007
DOI: 10.1159/000099142
|View full text |Cite
|
Sign up to set email alerts
|

Architectonic Arrangement of the Vasa Vasorum of the Human Great Saphenous Vein

Abstract: Objective: The detailed spatial arrangement of the vasa vasorum (VV) of the human great saphenous vein (HGSV) was demonstrated in qualitative and quantitative terms. Materials and Methods: Segments of the HGSV taken from cadavers 12–24 h post mortem and from patients undergoing aortocoronary bypassing were studied by light microscopy of India-ink-injected specimens and by scanning electron microscopy of vascular corrosion casts. Results: Arterial feeders were found to approach the HGSV from nearby arteries eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 49 publications
5
33
0
5
Order By: Relevance
“…Filling vessels with special materials is an established procedure and many different compounds have been reported so far. Besides the well-known polymerized methyl methacrylate resin (Anderson and Anderson, 1978;Gannon, 1981;Ohtani and Gannon, 1982), mostly PU4ii (Krucker et al, 2006) and Mercox-Cl-2B (Kachlik et al, 2002Lametschwandtner et al, 2004Lametschwandtner et al, , 2006Minnich et al, 2007) have been historically used. In the present study, we found that the combination of the method using the solution of ABS in butanone for microcopists with the method using the solution of formaldehyde in black Chinese ink for tissue sections would provide a satisfactory way for both planar and three-dimensional observations.…”
Section: Discussionmentioning
confidence: 99%
“…Filling vessels with special materials is an established procedure and many different compounds have been reported so far. Besides the well-known polymerized methyl methacrylate resin (Anderson and Anderson, 1978;Gannon, 1981;Ohtani and Gannon, 1982), mostly PU4ii (Krucker et al, 2006) and Mercox-Cl-2B (Kachlik et al, 2002Lametschwandtner et al, 2004Lametschwandtner et al, , 2006Minnich et al, 2007) have been historically used. In the present study, we found that the combination of the method using the solution of ABS in butanone for microcopists with the method using the solution of formaldehyde in black Chinese ink for tissue sections would provide a satisfactory way for both planar and three-dimensional observations.…”
Section: Discussionmentioning
confidence: 99%
“…35 There are distinct qualitative differences between the AVV and the VVV. 36,37 The AVV are many fewer in number, with diameters ranging from 11.6 to 36.6 μm compared with the VVV diameter range of 11.1 to 200.3 μm. Vascular corrosion casts coupled with scanning electron microscopy show that the VVV change course at acute angles and form kinks, constrictions, and outpouchings.…”
Section: Vasa Vasorum Structure/functionmentioning
confidence: 99%
“…37 The autonomic nervous system is thought to control blood flow in the human saphenous vein vasa vasorum. 35,37 Use of the saphenous vein for coronary artery bypass graft surgery is associated with spasm of vascular smooth muscle cells (SMCs) of the vein that can develop into vein-graft disease. 38,39 The conventional surgical technique for saphenous vein harvest involves stripping the connective tissue from the vein, which injures the adventitial autonomic nerves and vasa vasorum 37,38 and may trigger venospasm.…”
Section: Vasa Vasorum Structure/functionmentioning
confidence: 99%
“…Further, that other factors are important in determining the density and penetration of vasa vasora. Such factors may include the activeness of the vessel wall in regulating blood flow (Chuncher & Somana); and metabolic activity (Kachlick et al, 2007). The overall cellularity and activity of the cells in other functions of the vessel wall such as remodeling, mechanical strength and immune surveillance, may also be important.…”
Section: Discussionmentioning
confidence: 99%